Multidisciplinary monitoring experiments at Kawah Ijen volcano - Gunawan, Hendra (2015)
“Wet volcanoes” with crater lakes and extensive hydrothermal systems pose challenges for monitoring and forecasting eruptions. That's because their lakes and hydrothermal systems serve as reservoirs for magmatic heat and fluid emissions, filtering and delaying the surface expressions of magmatic unrest.